Effectiveness of Implementing the Positive Thinking Modeling and Mindfulness Training Program in Depressed Caregivers of Autistic Children. - Chadaporn Kamfu; Patraporn Pattarasakoon; Hunsa Sethabouppha (International Journal of Child Development and Mental Health)
Long-term caregivers of children with autism may develop to depression. This study aimed to compare the mean scores for depression and positive thinking of caregivers of autistic children at baseline and at one month after receiving the positive thinking modeling and mindfulness training program. The sample included 30 caregivers of autistic children who were purposively selected. Data were collected using the Depression Scale-9Q and the Positive Thinking Scale. Data were analyzed using descriptive statistics and the Wilcoxon signed rank test.